Local Legal Instruments and the Challenge of Implementing Village Authority in Decentralized Indonesia - Mohi, Fadliyanto; Lahaling, Hijrah; Djafar, Marwan (IAIN Bone, 2025)
This study examines the effectiveness of Regent/Mayor Regulations (Peraturan Bupati/Walikota) as implementing instruments of village authority under the framework of Law No. 6 of 2014 on Villages and Minister of Home Affairs Regulation No. 44 of 2016. Using a normative legal research method with statutory and conceptual approaches, the analysis focuses on two comparative cases in Gorontalo Province. The findings reveal a stark disparity in regulatory quality: while the Gorontalo Regency regulation remains administrative and formalistic, the North Gorontalo regulation adopts a more participatory and context-sensitive approach, integrating local cultural values and traditional practices. The absence of operational technical guidelines from the central government and limited regulatory capacity at the local level have hindered the realization of the principles of recognition (rekognisi) and subsidiarity. This study concludes that a prescriptive, participatory, and locally responsive regulatory approach is essential for ensuring that Regent/Mayor Regulations function as effective instruments for actualizing village autonomy. The research recommends that future legal reforms provide clear technical guidance and promote inclusive governance frameworks that reflect the diversity of village contexts across Indonesia.